El virus más letal: la necesidad de una adecuada regulación sobre las fake news en el Perú - St. Laurent del Castillo, Jacqueline Rose; Robles Vargas, Antonio Sebastián (Pontificia Universidad Católica del Perú, 2021)
New technologies have led to a 180 degree turn in the way society shares, consumes and accesses information. However, just as the media has contributed to personal and social development, the panorama in recent years has changed as a result of the growing wave of false information on the internet.In this article, the authors determine the risks involved in spreading fake news about the COVID-19 pandemic and assess whether current national legislation, based on what international parameters have established, manages to mitigate this issue that has forced even the most developed legislations in the world to modify the scope and effects of their regulations.

Las nuevas tecnologías han supuesto un giro de 180 grados en la forma en que la sociedad comparte, consume y accede a la información. No obstante, así como los medios de comunicación han contribuido al desarrollo social y personal, el panorama en los últimos años ha cambiado a causa de la creciente ola de información falsa en internet.En el presente artículo, los autores determinan los riesgos que conlleva la difusión de noticias falsas a propósito de la pandemia del COVID-19 y evalúan si la legislación nacional vigente, a partir de lo que disponen los parámetros internacionales, es la adecuada para combatir esta problemática que ha obligado incluso a las legislaciones más desarrolladas del mundo a modificar los alcances y efectos de su normativa.
The most lethal virus: the need for an adequate fake news regulation in Peru
Keywords: Fake news; Derecho internacional; Derecho penal general; Libertad de expresión; https://purl.org/pe-repo/ocde/ford#5.05.01